MODELING OF PIEZORESISTIVE EFFECT IN COMPENSATED SILICON WITH DEEP NICKEL AND MANGANESE IMPURITIES UNDER HYDROSTATIC PRESSURE - R. Khamidov,; A. Suvanov, (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract This study develops a theoretical model to describe the piezoresistive effect in silicon compensated with deep-level impurities, specifically nickel (Ni) and manganese (Mn), under hydrostatic pressure. The research is motivated by the need for stable semiconductor strain sensors operable in harsh environments. Based on provided experimental data, the model formulates the relationship between applied pressure and changes in resistivity, carrier concentration, and mobility. The core of the theory involves the pressure-induced shift of deep impurity energy levels and its effect on carrier ionization. Analysis shows that the significant decrease in resistivity in Si and Si under pressure is predominantly due to a substantial increase in free carrier concentration, particularly in highly compensated samples. The model successfully explains the distinct behavior of electron and hole mobility in n-type and p-type materials. The results confirm that the piezoresistive sensitivity in deeply compensated silicon is primarily a concentration-driven phenomenon, providing a basis for designing advanced strain-sensitive devices.